2010
DOI: 10.1094/mpmi-23-1-0039
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Induction and Role of Mitochondrial Alternative Oxidase and Nitric Oxide in a Compatible Tomato–Tobacco mosaic virus Interaction

Abstract: The role of mitochondrial alternative oxidase (AOX) and the relationship between AOX and nitric oxide (NO) in virus-induced systemic defense to Tobacco mosaic virus (TMV) were investigated in susceptible tomato (Solanum lycopersicum) plants. TMV inoculation to the lower leaves induced a rapid NO synthesis and AOX activation in upper uninoculated leaves as early as 0.5 day postinoculation. Application of exogenous potassium cyanide (KCN, a cytochrome pathway inhibitor) at nonlethal concentrations and NO donor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 63 publications
6
46
0
1
Order By: Relevance
“…The induction of AOX1a in the cys-c1 mutant in nonstressed conditions could prepare it to better respond to a pathogen attack, probably by inducing a signal transduction dependent on ROS that culminates in the induction of defense proteins such as PR1 and other proteins related to pathogenesis. It has been suggested that tobacco and tomato cyanideinduced resistance to virus is mediated by AOX, which would contribute to the signal transduction pathway leading to resistance (Chivasa and Carr, 1998;Fu et al, 2010). Strikingly, when overexpressing either the native AOX or a version of AOX mutated at its active site, tobacco mosaic virus vectors increase systemic movements in Nicotiana benthamiana (Murphy et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The induction of AOX1a in the cys-c1 mutant in nonstressed conditions could prepare it to better respond to a pathogen attack, probably by inducing a signal transduction dependent on ROS that culminates in the induction of defense proteins such as PR1 and other proteins related to pathogenesis. It has been suggested that tobacco and tomato cyanideinduced resistance to virus is mediated by AOX, which would contribute to the signal transduction pathway leading to resistance (Chivasa and Carr, 1998;Fu et al, 2010). Strikingly, when overexpressing either the native AOX or a version of AOX mutated at its active site, tobacco mosaic virus vectors increase systemic movements in Nicotiana benthamiana (Murphy et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Palmieri et al (2010) provided evidence for the cross talk between NO and mitochondria in activating the stress-related response in plants. The study of Fu et al (2010) highlighted a role for transcriptional activation of mitochondrial AOX in triggering systemic basal defenses against Tobacco mosaic virus. The data presented here suggested the involvement of NO in mediating the expression of the AOX gene and the upregulation of antioxidant enzyme activities.…”
Section: No-mediated Maintenance Of Redox Homeostasis Contributes To mentioning
confidence: 99%
“…Alternative oxidase (AOX) activation plays a role in detoxification of the harmful effect of reactive oxygen species (ROS) and in the maintenance of cellular redox homeostasis under adverse stresses (Moore et al, 2002). Fu et al (2010) demonstrated the cross talk of mitochondrial AOX and NO in the induction of antiviral defense response against tobacco mosaic virus infection. These findings indicate that NO is possibly connected with antioxidant mechanisms that underlie elicitor-induced cellular responses.…”
mentioning
confidence: 99%
“…The alternative pathway bypasses two proton translocation sites at complexes III and IV and transfers electrons directly from the reduced forms of ubiquinone to O 2 via AOX, thus yielding only limited ATP production (Moore and Siedow 1991). AOX was initially identified in the thermogenic flowers of Araceae but has since been described in many other plant species and tissues, especially in response to biotic and abiotic stresses, including chilling, ozone, pathogen attack or treatment with exogenous elicitors, such as harpin (Ederli et al 2006;Vidal et al 2007;Watanabe et al 2008;Király et al 2008;Song et al2009;Fu et al 2010). Several lines of evidence, particularly those results obtained with transgenic tobacco and Arabidopsis, have suggested that AOX may serve a general function by limiting the formation of mitochondrial reactive oxygen species (mROS) (Maxwell et al 1999;Navrot et al 2007).…”
Section: Introductionmentioning
confidence: 99%